Safety and preliminary efficacy of allogeneic bone marrow-derived multipotent mesenchymal stromal cells for systemic sclerosis: a single-centre, open-label, dose-escalation, proof-of-concept, phase 1/2 study. (February 2022) - Farge, Dominique; Loisel, Séverine; Resche-Rigon, Matthieu; Lansiaux, Pauline; Colmegna, Ines; Langlais, David; Charles, Catney; Pugnet, Grégory; Maria, Alexandre Thibault Jacques; Chatelus, Emmanuel; Martin, Thierry; Hachulla, Eric; et al.
Summary: Background: Systemic sclerosis remains an orphan life-threatening autoimmune disease. The unique immunomodulatory, proangiogenic, and antifibrotic properties of mesenchymal stromal cells provide a strong rationale for mesenchymal stromal cell-based therapy for systemic sclerosis, and treatment with mesenchymal stromal cells has shown benefits in preclinical models of this disease. The safety of allogeneic bone marrow-derived mesenchymal stromal cell administration in patients with severe systemic sclerosis has not yet been established. We aimed to test the safety and feasibility of a single intravenous injection of intrafamilial allogeneic bone marrow-derived mesenchymal stromal cells to treat severe diffuse systemic sclerosis. Methods: We did an open-label, dose-escalation, proof-of-concept, phase 1/2 study at Saint-Louis-Hospital, Paris, France. Eligible patients were aged 18–70 years with severe diffuse systemic sclerosis, who fulfilled the 2013 American College of Rheumatology and European League Against Rheumatism systemic sclerosis criteria, had a minimum modified Rodnan skin score of 15 (range 0–51), had severe lung, heart, or kidney involvement, and had inadequate response or contraindications to conventional immunosuppressive therapy or autologous haematopoietic stem cell transplantation. Patients with severe comorbidities were excluded. The first ten recipients were to receive a single intravenous infusion of 1 × 10 6 bone marrow-derived mesenchymal stromal cells per kg bodyweight, and the subsequent ten recipients were to be infused with a single dose of 3 × 10 6 bone marrow-derived mesenchymal stromal cells per kg bodyweight. The primary endpoint was immediate tolerance during infusion and within the first 10 days after infusion, measured as the occurrence of serious adverse events (grade 3 or higher) in all infused patients. Safety was assessed in all participants during the 24-month follow-up period. This study is registered with ClinicalTrials.gov, NCT02213705 . Findings: Between March 24, 2014, and Jan 6, 2020, 20 cisgender individuals (13 women and seven men) with severe diffuse systemic sclerosis were enrolled. All 20 patients were included in the primary outcome analysis. No infusion-related severe adverse events and three infusion-related adverse events occurred in the first 10 days after treatment; one patient had grade 1 flushing and another patient had grade 1 nausea and grade 2 asthenia. After ten days and up to a median follow-up of 24·1 months (IQR 20·8–24·5), 36 non-treatment-related severe adverse events in 14 (70%) patients and no treatment-related adverse event were reported. Interpretation: A single infusion of allogeneic bone marrow-derived mesenchymal stromal cells was safe in patients with severe diffuse systemic sclerosis. Future placebo-controlled trials will help to definitively ascertain the efficacy of mesenchymal stromal cell-based cell therapy from various tissue sources in larger number of patients with systemic sclerosis. Funding: French Ministry of Health, Capucine Association, Fonds de Dotation de l'AFER pour la Recherche Médicale, and Agence Nationale de la Recherche (Infrastructure Program Ecell), France.